Spatial resolution threshold in layers and red jungle fowls : are there differences due to light intensity or light spectra? - Annerstedt, Pauline (SLU/Dept. of Animal Environment and Health (until 231231), 2018)
The domestic fowl (Gallus gallus domesticus) originates from the forests in South-east Asia. It may be correct to assume that the visual system of the domestic fowl is still adapted to light that is filtered through the green forest canopy. In modern poultry production, however, light is provided via artificial luminaires and in low intensities to control feather pecking and cannibalism. Compared with production and reproduc-tion, the effect of light intensity on visual abilities is not researched as much. The aim with this study was to compare spatial resolution threshold between layers and its ancestor the red jungle fowl, between different light spectra and light intensities.